Inovasi pelayanan era new normal di Dinas Perpustakaan dan Kearsipan Kota Cirebon - Rian Gunawan (Jurnal Informatio, 2022)
The presence of the New Normal era is not only a solution to reducing the tension of the Covid-19 pandemic and creating a new order of life but also a challenge for various sectors that must continue. The closure of the library building should not be a reason for libraries to stop providing information services to the public. The Cirebon City Library and Archive Service (Dispusip) continues to adapt to changes and strive to implement services to keep running. This study aimed to find out the form of Cirebon City Dispusip's innovation and obstacles during the Covid-19 pandemic. This study used a descriptive qualitative approach. Data collection techniques were carried out through field observations, direct interviews, and literature studies. The informants selected in this study were two employees at the Cirebon City Dispusip. The study results indicated that in the implementation of library services during the Covid-19 pandemic, the Cirebon City Office of Education had made innovations in the form of online services. They included several types of services, namely offline visiting services with limited quotas, online circulation services, online membership services, digital library application services, as well as digital-based creative literacy programs. The obstacle faced by the Cirebon City Dispusip in implementing online service innovations was the problem of system/server errors. The existence of online service innovations that have been implemented has enabled services at the Cirebon City Dispusip to continue running even in a pandemic.